(untitled) (European Journal of Pure and Applied Mathematics, 2018)
In this paper, a new class of operators called quasi n-class Q and quasi n-class Q* operators are introduced and studied some properties. Quasi n-class Q and quasi n-class Q*Â composition and weighted composition operators on L2() and H2() are characterized. Also weÂ discuss quasi n-class Q and quasi n-class Q composite multiplication operator on L2 space andÂ Aluthge transformation of these class of operators are obtained.